2014
DOI: 10.1097/pcc.0000000000000076
|View full text |Cite
|
Sign up to set email alerts
|

The Parent Perspective

Abstract: Objective To identify factors important to parents making decisions for their critically ill child. Design Prospective cross-sectional study. Setting Single center, tertiary care PICU. Subjects Parents making critical treatment decisions for their child. Intervention One-on-one interviews that used the Good Parent Tool-2 open-ended question that asks parents to describe factors important for parenting their ill child and how clinicians could help them achieve their definition of “being a good parent” t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
71
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 134 publications
(74 citation statements)
references
References 23 publications
1
71
0
2
Order By: Relevance
“…A previous study 36 implemented this discrete-choice methodology to assess 43 parents of patients in a pediatric intensive care unit. The findings of the study indicated that making informed medical decisions was rated as the most important attribute for fathers and for mothers who did not identify a decision-making partner; however, mothers who identified themselves as being a member of a couple rated focusing on the child’s health and putting child’s needs above my own as the most important attributes.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study 36 implemented this discrete-choice methodology to assess 43 parents of patients in a pediatric intensive care unit. The findings of the study indicated that making informed medical decisions was rated as the most important attribute for fathers and for mothers who did not identify a decision-making partner; however, mothers who identified themselves as being a member of a couple rated focusing on the child’s health and putting child’s needs above my own as the most important attributes.…”
Section: Discussionmentioning
confidence: 99%
“…Parents often sought reassurance from physicians and other health professionals during bereavement meetings that they were indeed good parents. Hinds and colleagues (2009) and October, Fisher, Feudtner & Hinds (2014) previously described the concept of trying to be a good parent to children with terminal cancer and children with life-threatening conditions in PICUs, respectively. Among parents of children with terminal cancer, “doing right by my child” was the most frequently mentioned aspect of being a good parent (Hinds et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Among parents of children with terminal cancer, “doing right by my child” was the most frequently mentioned aspect of being a good parent (Hinds et al, 2009). Among parents of children in PICUs, “focusing on my child’s quality of life,” “advocating for my child,” and “putting my child’s needs above my own” were most frequently mentioned (October et al, 2014). Aspects of being a good parent identified in the current study overlap with these findings and include self-sacrifice, knowledge of the child’s condition, and a focus on the child’s quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Trust in the medical and research teams is fundamental to why families agree to participate in research (8385). When family values, preferences and perspectives are understood by researchers (86, 87), most families will cite altruism in allowing their children to participate in research (85, 88, 89), even in the absence of potential direct benefit (90). …”
Section: Approachmentioning
confidence: 99%